LEGAL ASPECTS FOR LATVIAN ENTERPRISES, ATTRACTING FINANCE VIA CROWDFUNDING PLATFORMS - Vanaga, Aija; Zarembo, Imants (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
When financial resources are decreasing, crowdfunding is an opportunity to deliver product and service to export markets, meet future buyers and attract financial resources. Latvian companies have considerably limited opportunities in crowdfunding markets, as some are not legally accessible. Therefore, it is an important research question to what extent Latvian companies can be using mainly international crowdfunding platforms to attract financial resources.